Manajemen Relasi Sosial Pesantren-Walisantri: Dialektika Adab dan Keterbukaan sebagai Basis Etika Komunikasi - Muhammad Bakron Andre Setiawan (Visionaria: Journal of Educational Innovation Management, 2025)
Social transformation and digital communication have fundamentally reshaped the relationship between Islamic boarding schools (pesantren) and students’ parents (walisantri). This study aims to analyze the patterns of social relations within the Qur’anic Education Center (PPIQ) of Nurul Jadid Islamic Boarding School, identify the value tensions between adab (moral courtesy) and openness in institutional communication practices, and formulate a value-based management model grounded in ethical communication. Using a qualitative case study approach, the research involved administrators, teachers, and representatives of walisantri as participants. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using Miles and Huberman’s interactive model with source triangulation to ensure validity. The findings reveal a transitional pattern of social relations that balances moral authority with social participation. The novelty of this study lies in the development of a value-based management model that integrates the principles of adab, openness, and balance as the ethical framework of institutional communication. This model contributes to strengthening pesantren governance that is ethical, transparent, and adaptive to modern social dynamics.